If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 36 + -9x = 45 Solving 36 + -9x = 45 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-36' to each side of the equation. 36 + -36 + -9x = 45 + -36 Combine like terms: 36 + -36 = 0 0 + -9x = 45 + -36 -9x = 45 + -36 Combine like terms: 45 + -36 = 9 -9x = 9 Divide each side by '-9'. x = -1 Simplifying x = -1
| x-36=30 | | 6a+3a-5a-b= | | x+29=12 | | x-3x-6=-x | | 12a^3+39a^2-36a= | | x+8x-2=3x | | y=1.2x-3.8 | | 100-15=2.5h | | Z/3=5/3 | | 22=3x+4 | | 50x=3 | | -48=6(a) | | 300(x)=5x-120 | | 1/6(x-20)=20 | | 5c-15=2c+7 | | x-(5/6)=4x+(1/8) | | 10x+21(x-2)=113 | | 1/x+3/x+2+6/8x+4 | | 13=m/-5 | | 7m=12 | | 15+.25=20+.05 | | 8+3k=4k-3 | | 0.3x-0.3(3-x)=0.6 | | 2x+17+x+5=97 | | (9m-2n)(5m+8n)= | | m=12 | | 1/2a+1/a | | p(50)=5(50)-120 | | 6x+12=6x-12 | | 1+1/x^2-20/x^4=0 | | 4x^3+24x^2+74x+50=0 | | 18b-24b=-36 |